The Spatial Characteristics of Tidal Flood Vulnerability and Adaptation Strategy in Tambak Lorok Kampung Settlement - Fajrin, Akhmad Raditya Maulana; Hayati, Arina; Faqih, Muhammad (Institut Teknologi Sepuluh Nopember, 2020)
The coastal area has an important role in supporting the community development and economics. The problem occurs when the tidal flooding has almost completely engulfed human activities for instance in human settlements. Tidal flooding has a negative impact on physical, social, economic, and environmental conditions, as an example the coastal settlement in Tanjung Mas Village. Tidal flood, in addition, can cause damage on infrastructure and housing areas, also, it has an impact to the live of communities, households, and individuals simultaneously. This research aims to examine on how to determine the vulnerability of community settlements to the danger of tidal flooding and how to build the adaptation efforts among the community to deal with tidal flooding disaster in order to keep the buildings and public facilities in safety. This research uses interview and observation methods, then, by using qualitative descriptive techniques to gain result underlined in the object research. The result shows that Kampong Tambak Lorok can be divided into 3 zones at high, medium and low. This zoning concept is obtained from flood vulnerability assessment related to the high of tidal flood, inundation duration and its impact. The first zone is represented by a high tidal flood with an average threat duration of inundation ranging from 3 to 5 hours. The depth of the tidal flooding can reach around 70-80 cm from the floor in a house. The second zone is represented by a medium tidal flooding with an average threat duration of inundation ranging from 3 to 4 hours. The depth of the Tidal Flood can reach around 50-60 cm from the floor. The third zone is a low tidal flooding with an average threat of inundation ranging from 0 to 1 hour. The problem of settlements on monetary and non-monetary factors lies in the economic capacity of the community which is classified as very low, affecting the value of expenditure for settlement needs. This has an impact on the response of the community in dealing with tidal flooding. Adaptation to settlements by elevating the level of floor in the house, changing the position of electricity, elevating the height of the house, making dykes on the front of the house and suctioning the flood by pump.